2022
DOI: 10.1002/dta.3231
|View full text |Cite
|
Sign up to set email alerts
|

A calibration friendly approach to identify drugs of abuse mixtures with a portable near‐infrared analyzer

Abstract: Both the increasing number and diversity of illicit-drug seizures complicate forensic drug identification. Traditionally, colorimetric tests are performed on-site, followed by transport to a laboratory for confirmatory analysis. Higher caseloads increase laboratory workload and associated transport and chain-of-evidence assurance performed by police officers. Colorimetric tests are specific only for a small set of drugs.The rise of new psychoactive substances therefore introduces risks for erroneous results. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…Combined with the conclusions from earlier work on cocaine, 17 the results in this study show that the calibration friendly data analysis approach based on dedicated matrix libraries and mixture detection works sufficiently for various types of drugs-of-abuse casework.…”
Section: Conclusion and Future Outlooksupporting
confidence: 72%
See 4 more Smart Citations
“…Combined with the conclusions from earlier work on cocaine, 17 the results in this study show that the calibration friendly data analysis approach based on dedicated matrix libraries and mixture detection works sufficiently for various types of drugs-of-abuse casework.…”
Section: Conclusion and Future Outlooksupporting
confidence: 72%
“…They showed that MDMA detection is possible using PLS modeling 33–35 . It is noteworthy that the reported MDMA HCl spectrum in these studies was different from the spectra recorded by our group 17,36 . These differences were attributed to different hydrated and anhydrous polymorphous forms of MDMA HCl 35,37 .…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations